Motivasi dan Persepsi Mahasiswa Pendidikan Guru dalam Memilih Mengajar sebagai Karir Masa Depan - Afdhal Fatawuri Syamsuddin; Hardianto Rahman; Faidah Yusuf (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aimed to explore the motivations and perceptions of student teachers in choosing teaching as a career. A cross-sectional survey was conducted among students from four groups based on year of entry. Using the FIT-choice scale, participants' motivational factors were assessed. Descriptive analysis showed that intrinsic factors, such as the desire to become a teacher and enjoyment of working with children, strongly influenced their motivation. They also perceived teaching as a demanding yet rewarding profession with high social status. Despite recognizing the relatively small salaries of teachers and the persuasion to choose other careers, the participants expressed high satisfaction with their choice. These findings underscore the importance of intrinsic rewards, the need to address salary concerns, and the importance of a supportive environment in attracting and retaining motivated individuals in the teaching profession. The results of this study have implications for educational institutions and policy makers in improving teacher recruitment and retention strategies